2020
DOI: 10.1016/j.celrep.2020.107771
|View full text |Cite
|
Sign up to set email alerts
|

STING Gain-of-Function Disrupts Lymph Node Organogenesis and Innate Lymphoid Cell Development in Mice

Abstract: STING gain-of-function causes autoimmunity and immunodeficiency in mice and STING-associated vasculopathy with onset in infancy (SAVI) in humans. Here, we report that STING gain-of-function in mice prevents development of lymph nodes and Peyer's patches. We show that the absence of secondary lymphoid organs is associated with diminished numbers of innate lymphoid cells (ILCs), including lymphoid tissue inducer (LTi) cells. Although wild-type (WT) a4b7 + progenitors differentiate efficiently into LTi cells, STI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…Reduced numbers and anti-proliferative effects in T cells have also been observed in patients with SAVI, although these features are less prominent compared with what is seen in mice 48 , 114 . Notably, ablation of type I interferon signalling or disabling necroptosis had no effect on the disease pathogenesis in the N153S mouse model of SAVI, whereas depletion of T cells protected N153S mice from developing lung disease 120 , 122 124 . The extent to which the clinical manifestations seen in humans rely on type I interferon signalling or on T cell-mediated immunopathology is not yet clear.…”
Section: Activation Of Cgas–sting In Disease Contextsmentioning
confidence: 98%
“…Reduced numbers and anti-proliferative effects in T cells have also been observed in patients with SAVI, although these features are less prominent compared with what is seen in mice 48 , 114 . Notably, ablation of type I interferon signalling or disabling necroptosis had no effect on the disease pathogenesis in the N153S mouse model of SAVI, whereas depletion of T cells protected N153S mice from developing lung disease 120 , 122 124 . The extent to which the clinical manifestations seen in humans rely on type I interferon signalling or on T cell-mediated immunopathology is not yet clear.…”
Section: Activation Of Cgas–sting In Disease Contextsmentioning
confidence: 98%
“…Subsequently, the impaired proliferation of T cells and other immune cells would cause severe innate and adaptive immunodeficiency to exacerbate the severity of SAVI. Recent studies have suggested that the reason for the T-cells deficiency caused by STING activation may be STING activation disrupt the calcium homeostasis or the migration of progenitors to the thymus ( 88 , 89 , 92 , 93 ). These findings suggested that STING was a critical factor in the occurrence and development of the SAVI via regulating the proliferation and differentiation of the T cells.…”
Section: Autoimmune and Inflammatory Diseasesmentioning
confidence: 99%
“…A representative example is that acquired mutations of the STING gene (STING N154S in humans and STING N153S in mice) cause STINGassociated vasculopathy with onset in infancy (SAVI), characterized by vasculopathy, ulcerative skin lesions, and pulmonary fibrosis, spontaneous colitis (86)(87)(88)(89)(90)(91). In the SAVI model, STING activation led to a cell-intrinsic T-cells defect (CD4 + and CD8 + T cells) via regulating the differentiation of progenitor cells and the lifespan of mature T cells (88,92). Subsequently, the impaired proliferation of T cells and other immune cells would cause severe innate and adaptive immunodeficiency to exacerbate the severity of SAVI.…”
Section: Autoimmune and Inflammatory Diseasesmentioning
confidence: 99%
“…Lung disease in the N153S mice appeared to be T-cellmediated, since Rag1 −/− STING N153S mice, which lack T cells and mature B cells, exhibited no histological evidence of lung disease and Tcrβ −/− STING N153S mice developed only very mild lung disease [60,61]. A disruption in the development of second lymphoid organs and, consequently, a reduction of innate lymphoid cells in mice were also demonstrated [62]. These results suggest a central role of hematopoietic-derived cells in the lung disease of N153S mice.…”
Section: Savi Lung Disease Pathogenesismentioning
confidence: 93%